Preparation and characterization of chitosan-starch Janeng membranes cross-linking with citric acid. Issue 1 (February 2021) - Saiful; Mardiana, L; Rahmah, Z; Ajrina, M; Imanda, M R; Rahmi; Khairi; Ramli, M; Marlina
Abstract: Neat chitosan membranes have shortcomings in their application owing to weak mechanical properties, thus, requiring modification. In this study, a chitosan membrane was modified utilizing starch and cross-linking agent (citric acid) addition. The characterization of chitosan-starch membranes using Universal Testing Machine, Scanning Electron Microscope (SEM), Fourier Transform Infra-Red (FTIR), Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA) had proven the cross-linking formation. The cross-linked membrane had better tensile strength (11.07 kgf/mm 2 ) than the uncross-linked membrane (66.07kgf/mm 2 ). The DSC thermogram of uncross-linked and cross-linked membranes showed endothermic and exothermic peaks at different temperatures. In addition to the membranes' thermal characteristics, the DTA thermogram showed the decomposition process on the uncross-linked membrane uncross-linking occurred at a temperature range of 277.74-363.27 °C, while the decomposition of the cross-linked membrane was observed at a range of 287.83-356.38 °C. The FT-IR spectra confirmed a decrease in the intensity of the absorption peak associated with cross-linking formation within the membrane.